THE EFFECT OF REPLACING COMMERCIAL RATIONS WITH MAGGOT MEAL ON THE PERFORMANSNCE OF KUB CHICKENS - I G. A. A. S., Pratama; Wibawa, A. A. P. P.; Astawa, I P. A. (Jurnal Peternakan Tropika, 2024)
This research aims to evaluate the effect of replacing commercial feed with maggot meal on the performance of KUB chickens. The study was conducted in the barn owned by Drh. Guswan Br. Berawantangi Taman Desa Tukadaya, Melaya District, Jembrana Regency, Bali Province. A two-month study with four treatments and four replications was conducted utilizing a completely randomized design. For the four trials, we used four different proportions of commercial feed: 100% commercial feed (P0), 95% commercial feed (P1), 90% commercial feed (P2), and 85% commercial feed (P3). Among the metrics tracked were FCR (Feed Conversion Ratio), feed intake, weight increase, and ultimate body weight. Out of all the treatments, treatment P3 (consisting of 85% commercial feed and 15% maggot meal) had the highest final body weight, weight increase, feed intake, and feed conversion rate (P<0.05). The conclusion drawn is that replacing 10% and 15% of commercial feed with maggot meal in the KUB chicken diet can enhance the performance of KUB chickens, while replacing 5% of commercial feed with maggot meal yields performance equivalent to KUB chickens receiving only commercial feed without maggot meal.